A multidisciplinary learning experience contributing to mental health rehabilitation. Issue 1 (2nd January 2017) - Moxham, Lorna; Patterson, Christopher; Taylor, Ellie; Perlman, Dana; Sumskis, Susan; Brighton, Renee
Abstract: Purpose People who access health services often have a range of needs that require the involvement of members from a multidisciplinary team. Teaching future health professionals about the importance of a multidisciplinary approach can be challenging. The aim of this paper is to describe a project called Recovery Camp that enhanced multidisciplinary health education through experiential and immersive engagement with people experiencing mental illness.Method Future health professionals and people with a lived experience of mental illness took part in Recovery Camp — an innovative five-day therapeutic recreation initiative in the Australian bush. Results are presented in a case study format and provide the reflective quotes of participants. The quotes were analyzed using a content analysis to identify core concepts.Results Analyses identified a common appreciation of multidisciplinary learning. The interactions among students and between students and consumers, promoted inter-professional practice and a holistic understanding of mental health care.Conclusions An immersive multidisciplinary approach, embedded within a recovery-based programme, enhances students' understanding of the significance of multidisciplinary mental health care and treatment. Implications for Rehabilitation: People with a lived experience of mental illness have a range of complex needs that require involvement of members from a multidisciplinary rehabilitation team. This study suggested a multidisciplinary, experiential, immersive health education experience — drawing on the principles of therapeutic recreation — can promote inter-professional rehabilitative practice and an appreciation for holistic mental health care.